Impact of Metabolic Syndrome on Neuroinflammation and the Blood–Brain Barrier - Van Dyken, Peter; Lacoste, Baptiste (Frontiers in Neuroscience, 2018)
Metabolic syndrome, which includes diabetes and obesity, is one of the most widespread medical conditions today. It induces systemic inflammation, with far reaching effects on the body that are still being uncovered. Neuropathologies triggered by metabolic syndrome often result from increased permeability of the blood-brain-barrier (BBB). The BBB, a system designed to restrict entry of toxins, immune cells, and pathogens to the brain, is vital for proper neuronal function. Local and systemic inflammation induced by obesity or type 2 diabetes mellitus can cause BBB breakdown, decreased removal of waste, and increased infiltration of immune cells. This leads to disruption of glial and neuronal cells, causing hormonal dysregulation, increased immune sensitivity, or cognitive impairment depending on the affected brain region. Inflammatory effects of metabolic syndrome have been linked to neurodegenerative diseases. In this review, we discuss the effects of obesity and diabetes-induced inflammation on the BBB, the roles played by leptin and insulin resistance, as well as BBB changes occurring at the molecular level. We explore signalling pathways including VEGF, HIFs, PKC, Rho\ROCK, eNOS, and miRNAs. Finally, we discuss the broader implications of neural inflammation, including its connection to Alzheimer’s disease, multiple sclerosis, and the gut microbiome.